Relationships Among Cleaning, Environmental DNA, and Healthcare-Associated Infections in a New Evidence-Based Design Hospital. (8th July 2015) - Lesho, Emil; Carling, Philip; Hosford, Eve; Ong, Ana; Snesrud, Erik; Sparks, Michael; Onmus-Leone, Fatma; Dzialowy, Nicole; Fraser, Susan; Kwak, Yoon; Miller, Sonia; Chukwuma, Uzo; et al.
Abstract : OBJECTIVE: Hospital environments influence healthcare-associated infection (HAI) patterns, but the role of evidenced-based design (EBD) and residual bacterial DNA (previously thought to be clinically inert) remain incompletely understood. METHODS: In a newly built EBD hospital, we used culture-based and culture-free (molecular) assays, pulsed-field gel electrophoresis (PFGE), and whole-genome sequencing (WGS) to determine: (1) patterns of environmental contamination with target organisms (TOs) and multidrug-resistant (MDR) target organisms (MDR-TOs); (2) genetic relatedness between environmentally isolated MDR-TO and those from HAIs; and (3) correlation between surface contamination and HAIs. RESULTS: A total of 1, 273 high-touch surfaces were swabbed before and after terminal cleaning during 77 room visits. Of the 2, 546 paired swabs, 47% had cultivable biomaterial and 42% had PCR-amplifiable DNA. The ratios of TOs detected to surfaces assayed were 85 per 1, 273 for the culture-based method and 106 per 1, 273 for the PCR-based method. Sinks, toilet rails, and bedside tables most frequently harbored biomaterial. Although cleaned surfaces were less likely to have cultivable TOs than precleaned surfaces, they were not less likely to harbor bacterial DNA. The rate of MDR-TOs to surfaces swabbed was 0.1% (3/2546). Although environmental MDR-TOs and MDR-TOs from HAIs were genetically related by PFGE, WGS revealed that they were unrelated. Environmental levels of cultivable Enterococcus spp. and E. coli DNA were positively correlated with infection incidences (P<.04 and P<.005, respectively). CONCLUSION: MDR-TOs were rarely detected during surveillance and were not implicated in HAIs. The roles of environmental DNA and EBD, particularly with respect to water-associated fixtures or the potential suppression of cultivable environmental MDR-TOs, warrant multicenter investigations. Infect Control Hosp Epidemiol 2015;36(10):1130–1138